Effect of live fences of Gliricidia sepium on CO2 fluxes in tropical livestock systems. (December 2016) - Villanueva‐López, G.; Casanova‐Lugo, F.; Martínez‐Zurimendi, P.; Parsons, D.; Aguilar‐Solís, L. A.
Abstract: Live fences have the potential to improve microclimatic conditions, moderate soil CO2 fluxes and function as carbon sinks. We quantified variation in soil CO2 fluxes from livestock silvopastoral systems under the canopies of live fences (LF), formed by Gliricidia sepium trees, or artificial fences (AF). We determined the responses of soil CO2 fluxes to environmental factors, including diurnal and seasonal variations in temperature and relative humidity in each fencing system. Measurements were made from April to June (dry season) and from July to September (rainy season), 2012. Fluxes were similar between the two livestock systems; LF emitted 1.00 μmol CO2 /m 2 /s and AF 1.02 μmol CO2 /m 2 /s. Soil temperatures at 5 cm depth were 3% warmer in AF than in LF, and relative humidity was 16% greater in LF than in AF. Seasonal variation in temperature greatly affected soil CO2 fluxes, which changed seasonally in parallel with temperature of the topsoil and relative humidity at 1 m height, peaking in late summer. Fluxes in LF and AF were greater in the rainy season (1.1 μmol CO2 /m 2 /s, for both systems), when soil temperature was cooler and relative humidity was greatest, than during the dry season (0.9 μmol CO2 /m 2 /s, for both systems). Soil fluxes were larger at night (00:00–06:00 h), when soil temperature was cooler and relative humidity greater, than during the morning (6:00–12:00 h), when soil temperature was warmer and relative humidity was less. The presence of G. sepium trees in LF did not influence soil CO2 fluxes.